Revitalization Programs in Rural Areas in Kujawsko-Pomorskie Voivodship - Maria Kola-Bezka (Barometr Regionalny)
The aim of the article is to evaluate revitalization programs of rural communes in Kujawsko-Pomorskie Voivodship and to formulate critical remarks with respect to the revitalization programming rules currently in force. The method of analyzing source documents (i.e., revitalization programs, was used to achieve this objective). The subject of the analyzes were: revitalization models, ways of designating degraded areas and areas of revitalization as well as financial instruments and forms and methods of social participation provided for in the revitalization process. The results of the study indicate that the principles of revitalization programming, which may be effective in cities, do not always correspond to the conditions prevailing in rural areas, which is mainly due to the fact that these areas are usually mostly affected by a crisis caused by widespread occurrence of structural problems.